Em Direção a um Serviço de Replicação Transparente para Aplicações Web na Arquitetura J2EE - Zampieri, André; Cassol, Luciano Azevedo (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2006: Anais do VII Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2006.23345, 2006)
Due to the increasing complexity of computational systems, the use of development platforms has become very popular. They provide many services that allow developers to keep their focus of attention in the applications they are implementing. The J2EE platform is the technological solution by Sun Microsystems that provides support services for the development of Web applications. However, the J2EE platform doesn’t offer support to applications that have fault tolerance as a requisite. This work presents the use of Aspect-Oriented Programming to add transparently an objects replication service for applications developed under the J2EE platform.